Shining a spotlight on m6A and the vital role of RNA modification in endometrial cancer: a review - Jin, Zujian; Sheng, Jingjing; Hu, Yingying; Zhang, Yu; Wang, Xiaoxia; Huang, Yiping (Frontiers in Genetics, 2023)
RNA modifications are mostly dynamically reversible post-transcriptional modifications, of which m6A is the most prevalent in eukaryotic mRNAs. A growing number of studies indicate that RNA modification can finely-tune gene expression and modulate RNA metabolic homeostasis, which in turn affects the self-renewal, proliferation, apoptosis, migration and invasion of tumor cells. Endometrial carcinoma (EC) is the most common gynecologic tumor in developed countries. Although it can be diagnosed early in the onset and have a preferable prognosis, some cases might develop into metastatic or recurrent ones, with worse prognosis. Luckily, immunotherapy and targeted therapy are intended to bring good news to those endometrial cancer patients, gene modifications may have contributed to them, especially in the development of new targeted therapeutic genes and diagnostic biomarkers for EC. While current findings show the relationship between RNA modification and EC is still very limited, especially m6A. For example, what is the elaborate mechanism by which RNA modification affects EC progression. Taking m6A modification for example, what's the conversion mode of methylation and demethylation for RNAs and how to achieve selective recognition of specific RNA. These aspects for coping with various stimuli in vivo and in vitro, biological development, disease or tumor occurrence and development and other processes are valuable, RNA modifications represent a distinctive insight of genetic information, their roles in coping with various stimuli, biological development, disease, or tumor development in vivo and in vitro are self-evident, which may become a new direction for cancer in the future. In this review we summarize the category, characteristic and therapeutic precis of RNA modification, m6A in particular, with the purpose of seeking the systematic regulation axis related to RNA modification to provide a better solution for the treatment of EC.